Increased Lengths of Stay and Denial Rates Seen With Managed Care Organizations Following Total Hip Arthroplasty - Katanbaf, Reza; Swartz, Gabrielle N.; Dubin, Jeremy A.; Bains, Sandeep S.; Mont, Michael A.; Nace, James; Delanois, Ronald E. (The Journal of arthroplasty, 2025)
As Medicaid has expanded in response to the Affordable Care Act, managed care organizations (MCOs) have become the main health care delivery service for beneficiaries. These plans have prior authorization denial rates of over 12%. This finding warrants an ongoing evaluation of potentially modifiable barriers to access to care, such as denial rates, and how this restriction ultimately impacts patient care. This study compared patient characteristics, including age and the Charlson Comorbidity Index (CCI), lengths of stay (LOS), discharge dispositions, and denial rates following primary and revision total hip arthroplasty (THA) between patients who had MCOs and commercial insurance from 2020 to 2023. We reviewed our institutional database to identify patients who underwent primary or revision THA from 2020 to 2023. After excluding patients who had other insurance payer types, a history of hip fracture, and a history of malignancy, we identified 543 patients who underwent primary THA (MCO [n = 211]; commercial [n = 332]) and 96 patients who underwent revision THA (MCO [n = 26]; Commercial [n = 72]). We analyzed patient demographics (age and the CCI), LOS, and denial rates between the two cohorts for primary and revision THA. For patients who underwent primary THA, those who had MCO plans had similar CCIs (1.7 versus 1.7, P = 0.86) but were younger (54 versus 58 years, P < 0.0001) than those who had commercial plans, respectively. For patients who underwent revision THA, those who had MCO plans had a similar average age (53 versus 57 years, P = 0.25) and CCI (1.6 versus 1.7, P = 0.71) as those who had commercial plans, respectively. The average LOS was significantly higher in the MCO cohort compared to the commercial cohort for primary THA (2.5 versus 1.2, P < 0.0001) and revision THA (6.6 versus 2.9 days, P = 0.0001), respectively. The denial rate was significantly higher in the MCO cohort compared to the commercial cohort for primary THA (2.8 versus 0.7%, P < 0.0001) and revision THA (2.4 versus 0.6%, P < 0.0001), respectively. Lengths of stay and denial rates were higher in the MCO cohort than in the commercial cohort. This could lead to decreased provider participation and potentially serve as a barrier to care for patients who have MCO plans.